Assessing digital competence and inequalities among secondary school students in Sindh, Pakistan: Evidence from a mixed-methods study using DigComp 2.1 - Takbir Ali; Nooreen Aziz (Digital Theory, Culture & Society, 2026)
The rapid expansion of digital technologies has transformed the competencies required for education, employment, and civic participation. Although improvements in digital infrastructure across the Global South have reduced the first-level digital divide in access, disparities in digital skills continue to limit students’ meaningful engagement with digital learning. Despite growing policy attention, empirical evidence on students’ digital competencies in developing countries remains limited. This study examines the digital literacy competencies of secondary school students in Sindh, Pakistan. Using a convergent parallel mixed-methods design, Grade 10 students (n = 430) in Hyderabad were assessed using the DigComp 2.1framework. Quantitative data were collected through a DigCompSATbased questionnaire and complemented by semi-structured interviews with students (n = 47). The findings reveal a moderate level of digital literacy, with stronger competencies in information and data literacy but weaker skills in digital content creation, online collaboration, critical evaluation, safety, and problem-solving. Significant disparities were found across gender, geographic location, socioeconomic status, and access to digital resources, with male, urban, and higher socioeconomic status studentsdemonstrating greater digital competence. Access to personal digital devices and reliable internet connectivity emerged as significant predictors of digital competence. These findings provide evidence of digital skill inequalities and inform policies to promote equitable digital literacy development in secondary education.